Vector-borne disease and climate change adaptation in African dryland social-ecological systems - (:unkn) unknown (My University, 2019)
BackgroundDrylands, which are among the biosphere's most naturally limiting and environmentally variable ecosystems, constitute three-quarters of the African continent. As a result, environmental sustainability and human development along with vector-borne disease (VBD) control historically have been especially challenging in Africa, particularly in the sub-Saharan and Sahelian drylands. Here, the VBD burden, food insecurity, environmental degradation, and social vulnerability are particularly severe. Changing climate can exacerbate the legion of environmental health threats in Africa, the social dimensions of which are now part of the international development agenda. Accordingly, the need to better understand the dynamics and complex coupling of populations and environments as exemplified by drylands is increasingly recognized as critical to the design of more sustainable interventions.Main bodyThis scoping review examines the challenge of vector-borne disease control in drylands with a focus on Africa, and the dramatic, ongoing environmental and social changes taking place. Dryland societies persisted and even flourished in the past despite changing climates, extreme and unpredictable weather, and marginal conditions for agriculture. Yet intrusive forces largely out of the control of traditional dryland societies, along with the negative impacts of globalization, have contributed to the erosion of dryland's cultural and natural resources. This has led to the loss of resilience underlying the adaptive capacity formerly widely exhibited among dryland societies. A growing body of evidence from studies of environmental and natural resource management demonstrates how, in light of dryland system's inherent complexity, these factors and top-down interventions can impede sustainable development and vector-borne disease control. Strengthening adaptive capacity through community-based, participatory methods that build on local knowledge and are tailored to l
Keywords: African Research